A reference study to compare the methods of designing concrete mixes used in Libya - Abuisbuya, Abulgasem Yahya; Gbyayal, Mabrok (Journal of Pure & Applied Sciences, 2021)
Given the construction of concrete buildings and structures and the importance of concrete for construction on it, the process of manufacturing concrete requires the process of designing concrete mixtures when implementing and constructing these concrete structures. Which led to the importance of designing the concrete mixture and knowing the compressive strength of concrete and the quantities of materials such as cement, coarse and fine aggregates and the amount of water.The research presents a reference study on the implemented concrete mixes and their design methods in Libya in order to know their compressive strength after 28 days and the quantities of materials implemented in them and compare the results with each other in terms of the compressive strength of concrete and slumptest. And to know the design methods for the best mixtures in Libya and the possibility of using them and the differences between them. From the results of this study for all methods of designing the concrete mix implemented in Libya, the compressive strength of the implemented concrete is excellent.Where the highest value of the compressive strength of concrete was 47.53MPa by volumetric method, and the best value for the drop for operational was 20 mm, and therefore it is considered the greatest strength compared to the strength by other methods. Accordingly, from the results obtained in this research, the scalar design is considered the most appropriate design in Libya.